Metodo para determinacion de contenidos de materia seca y almidon en la yuca por el sistema de gravedad especifica - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
A rapid method of determining the percentage of DM and starch in cassava by the use of the specific root density is discussed, and a table, tested under Colombian conditions, is included for var. harvested from 10-12 mo. (CIAT)